PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP AGRESIVITAS PAJAK: PERAN MODERASI CORPORATE GOVERNANCE - Tiodora Theresa Horas Br Manurung; Dwi Ratmono (Diponegoro Journal of Accounting, 2023)
The objective of this study is to investigate the influence of corporate social responsibility (CSR) disclosure on tax aggressiveness and whether corporate governance moderates that influence. The variables used in this study are CSR disclosure as the independent variable, corporate governance as the moderating variable, and tax aggressiveness as the dependent variable. This study uses a sample of 2016-2021 manufacturing companies listed on the Indonesia Stock Exchange and Bloomberg Terminal with a total of 132 samples using purposive sampling with conditions that have already been determined. The analytical methods utilized in this study is the multiple regression analysis and absolute difference value. The results of this study showed that CSR disclosure has no influence over tax aggressiveness and that corporate governance weakens the negative influence which CSR disclosure has on tax aggressiveness.